Hydroponic farming and circular economy : implementation of circular economy into hydroponic production - Poznickova, Denisa (SLU/Dept. of Economics, 2019)
Vertical hydroponic farming presents an emerging industry that could soften the blow of conventional farming. Hydroponic farming is a form of controlled environment agriculture, which is usually situated indoors, and the plants grow in the absence of soil. Hydroponic production brings several benefits to the food system especially in terms of water use efficiency, space efficiency, all-year production and productivity of the system. Despite a number of benefits highlighted in the literature, there are challenges of hydroponic farming like dependency on energy to grow, a limited range of crops that are suitable for hydroponic production and higher price of the product. This study analyses the challenges that occur when the plants are grown at Urban Oasis hydroponic farm located in Stockholm, Sweden and explains how the concept of the circular economy could be implemented into the hydroponic farming production with the aim to address the identified challenges. This thesis follows a qualitative research design with an inductive approach. Ethnographic action research is carried out since the generated knowledge helps to promote the improvements in the business processes. The analysis of collected data from interviews and observations at Urban Oasis showed that the Swedish hydroponic farm may have better potential to make its production more sustainable, compared to the farms located in other countries. In Sweden, energy comes mostly from renewable sources and consumers are aware of environmental problems. In case of Urban Oasis, implementation of the circular economy is conditioned by mainly environmental and economic factors and the principle of reusing, reducing and recycling the resources is emphasised throughout all phases of production. The shift towards the circular economy can be successfully achieved through collective effort. Therefore, this thesis points out the potential for uptake of the concept of industrial symbiosis where synergy among businesses is developed and businesses can make use of someone else´s by-products.